A highly efficient heterogeneous copper-catalyzed chlorodeboronation of arylboronic acids leading to chlorinated arenes. Issue 2 (3rd January 2017) - He, Wen; Zhang, Rongli; Cai, Mingzhong
Abstract : A highly efficient heterogeneous copper-catalyzed chlorodeboronation of arylboronic acids with NCS for the synthesis of aryl chlorides has been described. Abstract : A highly efficient heterogeneous copper-catalyzed chlorodeboronation of arylboronic acids with inexpensive N -chlorosuccinimide (NCS) was achieved in MeCN in the presence of 10 mol% ofl -proline-functionalized MCM-41-immobilized copper(i ) complex [MCM-41-l -proline-CuCl] under mild conditions, yielding a variety of aryl chlorides in excellent yields. This method proved to be tolerant of a broad range of functional groups and particularly useful for the conversion of electron-deficient arylboronic acids to aryl chlorides, a transformation that is inefficient without copper catalysis. This heterogeneous copper catalyst can be recovered by a simple filtration of the reaction solution and recycled for at least 10 times without any decreases in activity.